The Influence of Marketing Strategy and Service Quality on Customer Loyalty at Bank BJB KC Majalengka - Tia Aprilia Susnita; Gita Kartika Sari; Tiara Rismayanti (Politeknik Mardira Indonesia, 2024)
This research aims to identify marketing strategies, evaluate service quality, and analyze their influence on customer loyalty at Bank BJB Majalengka Branch Office, Majalengka Regency. This research uses descriptive and verification methods with a quantitative approach to examine the relationship between marketing strategy, service quality and customer loyalty at Bank BJB Majalengka Branch. The population and sample in this study were 100 people. Data collection techniques include observation, interviews, and questionnaires.In this research, it was found that marketing strategies have a positive and significant influence on customer loyalty at Bank BJB Majalengka Branch Office. With a significance level of 0.05, the t value of 2.311 is greater than the t table value of 1.66140, which means the alternative hypothesis is accepted. These results indicate that investing in effective marketing strategies, such as building personal relationships, providing quality products, and providing a satisfying customer experience, can increase customer loyalty. Based on testing with a significance level (α) of 0.05, it was found that the tcount value for service quality was 4.632 which was greater than the ttable value of 1.66140. This means that the hypothesis which states that service quality has a significant effect on customer loyalty can be accepted. Thus, it can be concluded that service quality has a positive and significant influence on customer loyalty at Bank BJB Majalengka Branch Office. It can be concluded that marketing strategy and service quality have a positive and significant influence on customer loyalty at Bank BJB Majalengka Branch Office. With α=0.05, db1=2 and db 2=97, it is known that the F-table value is 3.09. From the values ​​above, it is known that the value of Fcount (56,812) > Ftable (3.09), so that H0 is rejected and Ha is accepted, meaning that marketing strategy and service quality together have a positive and significant effect on consumer loyalty.